Pemenuhan Hak Anak Keluarga Migran dalam Pengasuhan Alternatif Perspektif Keluarga Sakinah - Ahmad Ainur Bustomy; Israqunnajah Israqunnajah; Miftahul Huda (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
Labor migration causes some children to lose direct care from their biological parents so that childcare is transferred to surrogate families or Child Social Welfare Institutions (LKSA). The focus of this research is the implementation of the fulfillment of children's rights, alternative parenting mechanisms, and the relevance of the concept of the sakinah family in supporting the childcare of migrant families. This research is field research with a qualitative approach. The data was collected through observations, interviews, and documentation at the Social Service for Women's Empowerment and Child Protection of Lumajang Regency and LKSA under his guidance. The data were analyzed descriptive-analytically by relating field findings to the theory of childcare, fulfillment of children's rights, and the family of sakinah. The results of the study show that alternative parenting in Lumajang Regency is carried out through cooperation between families, local governments, communities, and LKSA to maintain the fulfillment of children's rights in the aspects of education, protection, health, emotional attention, and spiritual and moral development. LKSA implements a family-based parenting pattern through habituation of learning, worship, discipline, and daily mentoring. This study concludes that alternative parenting plays a role as a form of temporary protection as well as a means of character development for children of migrant families when the nuclear family is not able to carry out the parenting function optimally.